Evaluation of the Aerodramus fuciphagus and Aerodramus maximus edible birds nests' digestive enzymes - Mitin, Helen; Abdul Razak, Intan Shameha; Mohd Isa, Kamarudin; Abu Bakar @ Zakaria, Md Zuki (2012)
The swiftlets of Asia are known to use their saliva as nest building material during the breeding season. It is speculated that enzymes present in the saliva are the key valuable components of EBN for the possible medicinal and therapeutic effects. However, to our knowledge study on enzymes in EBN are unavailable. Thus, this study was conducted to determine the enzymatic profiling and presence of digestive enzyme contents in white and black EBN using the ApiZYM System as comparison. The ApiZYM (bioMèrieux, France) is a semi-quantitative micro method colour metric designed for the research of enzymatic activities.